Gestão das emoções em ambiente de serviço: uma análise dos comportamentos emocionais dos operadores em centrais de atendimento - Morais, Fabiano José de (2010)
The goal of this dissertation is to take look at the prism of the sociology of emotions the behavior patters like display rules and feeling rules adopted by the service staff at a Call Center. The sociological view on the agenda Will be based on the study conducted by the author Arlie Russel Hochschild, in your book with this title: “The Managed Heart: Commercialization of Human Feeling”. The book addresses the issue of emotional work and the postures adopted by people in private life and in a professional life, which can be denominated the emotional labor. The emotional labor especially happens in the professions of the sector services. Because of this, it is significant to survey the importance of the sector to provide services of the current economy, having knowledge of the variables involved in this activity and the roles of actors which is part off. From the standpoint of the characteristics of services, it will be presented concepts of schools coming from the Anglo-Saxon culture, strongly represented here by Valarie A. Zeitmal and Mary Jo. Bitner (2003). And also concepts of schools coming from the Nordic culture represented by the author Christian Grönroos (2009).